Incidence and treatment of positive pelvic sidewall lymph nodes in patients with rectal cancer. (14th July 2020) - Jones, H. G.; Radwan, R. W.; Sams, E.; Gibby, M.; Coomer, W.; Jeffries, J.; Codd, R. J.; Williams, G. L.; Taylor, G.; Horwood, J.
Abstract: Aim: The involvement of pelvic sidewall (PSW) lymph nodes in rectal cancer is a marker of locally advanced disease and poor prognosis. Eastern countries generally advocate lateral lymph node dissection (LLND) over the Western approach of neoadjuvant chemoradiotherapy and more limited surgery. The aim of this study was to evaluate how these advanced cancers were treated in three UK Health Boards. Methodology: This was a retrospective review of three colorectal multidisciplinary team meetings from 2008 to 2016. All patients with rectal cancer and suspicious PSW lymph nodes on pretreatment MRI were included. Results: There were 153 (6.2%) patients who met the inclusion criteria from a total of 2461 diagnosed rectal cancers. There was significant variability between the three centres with surgical intervention ranging from 59.2% to 84.4%, P = 0.015. There were 81 patients who had neoadjuvant chemoradiotherapy prior to surgery; of these 67 (82.7%) still had positive PSW nodes on the restaging MRI, but only 13 (19.4%) had LLND. There was no difference in local recurrence (15.3% vs 11.8%, P = 0.66), 5‐year overall survival (69.2% vs 80.1%, P = 0.16) or 5‐year disease‐free survival (69.2% vs 79.4%, P = 0.72) between patients having LLND and those receiving standard neoadjuvant treatment followed by total mesorectal excision surgery. Conclusions: This study has demonstrated that rectal cancer patients with PSW positive nodal disease have advanced disease, mostly of the lower rectum, and receive a highly heterogeneous spectrum of therapies, even within a relatively small geographical area. Greater accuracy in our preoperative staging is needed to select those patients who will benefit from LLND surgery.